Stock market development and integration in SADC (Southern African Development Community) - Sunil Kumar Bundoo (Review of Development Finance, 2017)
The paper analyses the extent of stock market integration in SADC by first analyzing beta and sigma convergence and then using cointegration analysis. The US market and the SSA index were used as benchmarks. The sample period was from January 1999 to December 2011 using daily market index data. We observe beta convergence but not sigma convergence; though the sigma values are falling for most of the SADC countries. Under normal conditions, no cointegrating vector was identified when using the US market as benchmark. When using the SSA index as benchmark one cointegrating vector was identified. The paper also takes stock of the extent of software and hardware stock market integration in SADC. The SADC stock exchanges must work towards greater integration so that they can attract more sustained portfolio flows rather than volatile portfolio flows and also greater FDI flows which are much needed for the financial and economic development of the SADC countries. We also need to consolidate and reduce the number of exchanges with the view to improve market capitalization, liquidity, market infrastructure, governance amongst others but most importantly to increase the visibility, robustness and reputation of SADC stock markets at the international level.
Keywords: G12; 650; Stock market; Mauritius